Diary of a hedgehog : - Biggs, Barton (Wiley, 2012)
The last book from investment legend Barton Biggs * Offers investors and business readers of all levels of experience new insights into the current economic crisis * Presents news ideas for readers looking to make the most of their money in the face of ongoing market turbulence Insightful and creative, Diary of a Hedgehog: Biggs Final Words on the Markets is the ultimate resource for anyone who wants to understand what's up with the market, where it's headed, and how to respond.